Maternal deaths due to eclampsia in teenagers: Lessons from assessment of maternal deaths in South Africa - Jagidesa Moodley; Nnabuike C. Ngene (AOSIS, 2020)
Background: Eclampsia remains a major cause of maternal mortality, particularly in teenage pregnancies. Healthcare professionals providing antenatal must regard teenagers as a high risk group for the pre-eclampsia-eclampsia syndrome. Setting: Data extracted from the South African Saving Mothers Report: 2014-2016. Aim: To establish the clinical details in teenage maternal deaths owing to eclampsia. Method: Retrospective review of the case records and maternal death assessment forms of teenagers that died due to eclampsia during 2014-2016. Results: There were 47 teenagers (aged 14 to 19 years) who died from eclampsia. Of these 18 out of 47 (38%) deaths occurred in the post-partum period. Forty (85.1%) of the patients had antenatal care. Three (6.4%) had post-partum eclampsia, and of the remaining 44 of the 47 (93.6%), the gestational age at first occurrence of a seizure ranged from 25 to 39 weeks. The blood pressures at the time of seizure ranged from systolic of 131 to 210 mmHg and diastolic of 89 to 130 mmHg. The commonest final causes of death were intracerebral haemorrhage associated with severe hypertension and multi-organ failure. Avoidable factors included transport delays, referral to the wrong levels of health care and poor care by health professionals. Conclusion: Teenage pregnancy is a risk factor for eclampsia-related death; awareness of borderline elevations of blood pressure levels from baseline values (prehypertension levels) and taking following national guidelines on the management of hypertensive disorders of pregnancy will decrease deaths from eclampsia.